Sex & gender: An introduction - Lips, Hilary M. (Waveland Press, Inc., 2020)
Are sex and gender really two different things? How malleable is gender identity? Do both gender and sex have to be conceptualized as binaries—as having two distinct but complementary categories? Should we emphasize gender differences, or is that the wrong question? When should we call a gender difference “small”? Are women really “nonaggressive” or does that label stem from stereotyping? How does subtle or “modern” sexism work on its targets? Scholarship on these and other gender-related questions has exploded in recent years. Hilary Lips synthesizes that research for students in an accessible and readable way. Concepts on sex and gender are presented with the social context in which they were developed. As in previous editions, Lips takes a multicultural approach, discussing the gender experiences of people from a wide range of races, cultures, socioeconomic statuses, and gender and sexual identities. She emphasizes empirical research but takes a critical approach to that research.
Keywords: analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; construction du savoir; corps; cours; discipline; discours dominant; essentialisation; hétérosexisme; identité; identité sexuelle; inégalités; premier cycle; psy4910; psychologie; santé; sciences humaines; sexe/genre; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; trs3550; études de genres

Gender: Psychological perspectives - Brannon, Linda (Routledge, 2017)
"Gender: Psychological Perspectives" synthesizes the latest research on gender to help students think critically about the differences between research findings and stereotypes, provoking them to examine and revise their own preconceptions. The text examines the behavioral, biological, and social contexts in which women and men express gendered behaviors. The text's unique pedagogical program helps students understand the portrayal of gender in the media and the application of gender research in the real world. -- From publisher's description. Contenu : Preface -- Acknowledgements -- About the author -- The study of gender -- Researching sex and gender -- Gender stereotypes: masculinity and femininity -- Hormones and chromosomes -- Theories of gender development -- Developing gender identity -- Intelligence and cognitive abilities -- Emotion -- Relationships -- Sexuality -- School -- Careers and work -- Health and fitness -- Stress, coping, and psychopathology -- Treatment for mental disorders -- How different? -- References -- Index.
Keywords: approches et analyses; biologie; comportements sexuels; cours; différence des sexes; discipline; discours dominant; identité sexuelle; maternité; paternité; premier cycle; psy4910; psychologie; relations amoureuses; santé; santé mentale; sciences; sciences humaines; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences sexuelles; études de genres

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Mon corps a-t-il un sexe? Sur le genre, dialogues entre biologies et sciences sociales - Gonthier, Josiane; Ruppli-Coursange, Mireille (Recherches (Paris. 1994), 2015)
"Sexe" est l'un des mots de la langue française que les gens sans distinction de classe, de religion, d'apparence ou de profession, utilisent avec grand intérêt, qu'ils soient accoudés au zinc d'un bistrot ou à la paillasse d'un laboratoire de biologie moléculaire. Deux mises en scène distinctes, sociale ou scientifique ; deux scénarios différents : d'un côté, les histoires d'amour ou d'imaginaire sexuel, de l'autre, les recherches biologiques. Sous ce mot de "sexe", notre langue, si riche, produit une polysémie bien fâcheuse. L'ambition de ce volume, qui rassemble les contributions de chercheurs et chercheuses en sciences de la vie et en sciences humaines et sociales est de faire le point sur les connaissances concernant le sexe biologique et ses variations, dont on sait désormais qu'il ne permet pas de séparer les individus en deux catégories bien distinctes. Ce livre veut aussi évaluer l'impact du genre sur le développement du corps des êtres sexués et sur la construction de leur identité. Enfin, il cherche à apprécier dans quelle mesure les croyances liées au genre (bicatégorisation mâle-femelle stricte, supériorité masculine) ont pu influencer les recherches menées sur le sexe biologique. Et les témoignages de personnes intersexes et transgenres apportent sur la question de l'identité sexuée un éclairage complémentaire qui bouscule les "réponses" que donnent le plus souvent la médecine et le droit.
Keywords: approches et analyses; biologie; corps; cours; discipline; discours dominant; premier cycle; psy4910; psychologie; pédagogie; queer; sciences; sciences humaines; sciences sociales; sexualité; systèmes d'oppressions; thématiques; épistémologie; études de genres

Cerveau, hormones et sexe : des différences en question - Cossette, Louise (Les éditions du remue-ménage, 2012)
Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d’ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l’information diffusée tient davantage du préjugé, du parti pris idéologique, que d’une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd’hui encore ?C’est de ce constat, et d’un certain sentiment d’exaspération, qu’est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S’appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l’orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d’auteures féministes. Il ne s’agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ? Des textes de Line Chamberland, professeure au département de sexologie de l’UQAM et titulaire de la Chaire de recherche sur l’homophobie de l’UQAM ; Louise Cossette, professeure au département de psychologie de l’UQAM et membre de l’Institut de recherches et d’études féministes (IREF) de l’UQAM ; Chantal Maillé, professeure à l’Institut Simone de Beauvoir à l’Université Concordia et Catherine Vidal, neurobiologiste, directrice de recherche à l’Institut Pasteur de Paris.
Keywords: Brain; Human behavior; LGBTQIA2+; Men; Psychology; Sex differences; Sex differences (Psychology); Women; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem7000; genre; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lit3220; premier cycle; psy4910; psychologie; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sexualité; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

The Sexualisation of Culture? - Gill, Rosalind (Social and Personality Psychology Compass, 2012)
This article examines contemporary debates about the ‘sexualisation of culture’. It sets out the context for claims that Western societies are becoming more sexualised and it explores a number of competing perspectives about sexualisation. It then looks in more detail at the nature of claims about sexualisation as they emerge from the different disciplinary perspectives of Psychology and Media and Cultural Studies, contrasting the strengths and weaknesses of each, and raising criticisms of both. In a final discussion section, the article considers the usefulness or otherwise of the notion of ‘sexualisation’ as analytic category and points to the need to go beyond polarised positions. It advocates a psychosocial approach that takes seriously differences and power in considering the contemporary proliferation of ‘sexualised’ images, practices and media
Keywords: approches et analyses; communication; corps; cours; discipline; discours dominant; discours médiatique; féminisme pop; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; systèmes d'oppressions; thématiques; études culturelles

Intimate Justice: A Critical Analysis of Sexual Satisfaction - McClelland, Sara I. (Social and Personality Psychology Compass, 2010)
This article elaborates an intimate justice framework to help guide research on sexual satisfaction. Using a critical historiography approach, I examine the etiology and development of the psychological construct of “satisfaction” over the last century and argue that social and political antecedents to satisfaction ratings are an essential and under-theorized aspect of research in this field. By examining what are considered to be the most influential definitions in life satisfaction research, I identify conceptual gaps, oversights, and disagreements that characterize this body of work, and specifically its theoretical treatment of inequity. Moving to the intimate domain, I argue that the field of sexual satisfaction must include theories and methods that systematically consider the role of social and sexual stigmas as antecedents to sexual satisfaction ratings. In the conclusion, building from existing social justice theories, I propose an intimate justice framework as a means to guide research that can highlight issues of entitlement and deservingness in sexual satisfaction research. This is particularly important as sexual satisfaction is increasingly used as an indicator of individual and relational well-being; however, this construct is presently limited and inadequately measured for women and men who experience limited sexual rights in the socio-political domain because of their gender and/or sexual minority status.
Keywords: approches et analyses; capacitisme; cours; discipline; intersectionnalité; justice sociale; premier cycle; psychologie; racisme; ressource en ligne; sciences humaines; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques

Diversité sexuelle et constructions de genre - Chamberland, Line; Frank, Blye W.; Ristock, Janice L. (Collection Santé et societé, 2009)
Les sciences sociales et épidémiologiques contemporaines tendent de plus en plus à prendre en compte la question du genre dans leurs théories sur les orientations sexuelles. Elle mettent ainsi en évidence les diverses articulations entre les formes de sexisme et d'homophobie, et leurs impacts différenciés selon les constructions du genre et les orientations sexuelles, de même qu'en fonction du contexte socioculturel dans lequel elles se situent. Réalisé avec l'appui de l'équipe pancanadienne Sexualités et genres, vulnérabilité et résilience (SVR), cet ouvrage regroupe des contributions de chercheurs francophones et anglophones du Québec, du Canada, de la France et de la Suisse romande, qui examinent les dimensions socioéconomiques, progessionnelles, familiales, relationnelles et psychologiques afin de saisir les variations liées au genre au sein des minorités sexuelles. Faisant appel à des résultats de travaux multidisciplinaires qui s'appuient sur des méthodologies de types quantitatif et qualitatif, ce livre met en lumière des processus contribuant aux inégalités sociales dans les champs de l'éducation, de l'économie et de la santé, et à des condition de vulnérabilité qui affectent l'estime de soi, les réseaux de soutien et la vie sociale. Les recherches observent des modes de résilience significatifs qui, là encore, peuvent varier en fonction du genre, suggérent ainsi sa prise en compte dans les interventions.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; lesbophobie; premier cycle; psy4910; psychologie; rapports sociaux de sexe; ressource en ligne; sciences humaines; sciences sociales; sexe/genre; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; théorie du genre; épistémologie; études de genres

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Life with the first baby: women's satisfaction with the division of roles - Cappuccini, G.; Cochrane, R. (Journal of Reproductive and Infant Psychology, 2000)
The ways parents divide their roles after their first child is born is a particularly complex arena. The success of negotiations within this close personal relationship may be central to the future of the new family. Women and their partners were surveyed in late pregnancy and 6 months after the birth. Their attitudes to role division remained largely non-traditional after the birth, even though most of them had incorporated some traditional elements into their behaviour. Emotional support received from their partners was important to women's satisfaction with role division, which had fallen only slightly after the birth. Eight of the women were interviewed in depth to explore why it might be that satisfaction with role division tended to remain high after the birth, despite the division usually not being what they had hoped for. Contributory factors may include changes in emphasis in the division of breadwinning and the maintenance of overall responsibility for traditional role areas despite sharing of tasks.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; europe; hétérosexualité; inégalités; maternité; premier cycle; privilèges; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Fantasies of femininity: Reframing the boundaries of sex - Ussher, Jane M. (Rutgers University Press, 1997)
In Fantasies of Femininity, Jane Ussher focuses on unraveling the contradictory visions of feminine sexuality: the fact that representations of the definition of woman seethe with sexuality yet for centuries women have been condemned for exploring their own sexual desires. In her quest for the sources of feminine representation, Ussher interviewed dozens of women - as well as some men - and combed popular media - from Seventeen to Cosmopolitan and Dallas to Donahue - to identify what shapes women's symbolic images of sex and femininity. Ussher argues that women have effectively resisted and subverted these archetypal fantasies of femininity, and in the process of so doing, reframed the very boundaries of sex. In this way, she exposes as myth much of what we think we know about "woman" and about "sex."
Keywords: approches et analyses; cours; discipline; fem1000; inégalités; premier cycle; psychologie; sciences humaines; sexualité; sexualité féminine; stéréotypes; systèmes d'oppressions; thématiques; études culturelles

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Collection Les Entêtées, 1983)
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis